(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Placental abruption is a significant obstetric emergency and a leading cause of antepartum hemorrhage, characterized by premature separation of the placenta from the uterine wall. It is associated with high maternal and perinatal morbidity and mortality, particularly in developing countries. This study aims to evaluate the fetomaternal outcomes in cases of placental abruption. Aims & Objectives: To evaluate the clinical presentation, risk factors, management, and fetomaternal outcomes in patients with placental abruption. Material & Methods: This retrospective case series was conducted at a tertiary care center over six months (January to June 2025). A total of nine pregnant women diagnosed with placental abruption were included. Clinical presentation, risk factors, management, and maternal and fetal outcomes were analyzed and summarized. Results: Most patients were aged 21–35 years. Hypertensive disorders of pregnancy and polyhydramnios were the most common risk factors. The predominant presenting symptoms included vaginal bleeding, abdominal pain, and decreased or absent fetal movements. Many patients had anemia, tachycardia, and elevated blood pressure. Emergency cesarean section was performed in cases with a live fetus, while vaginal delivery was preferred in stable patients with intrauterine fetal demise. Blood loss ranged from 1 to 2.5 liters, and all patients required blood transfusions. Maternal complications included postpartum hemorrhage, acute kidney injury, disseminated intravascular coagulation, and one case required peripartum hysterectomy. Perinatal outcomes were poor, with a high incidence of intrauterine fetal death and an overall mortality rate of 67%. Conclusion: The Placental abruption remains a life-threatening condition with significant adverse maternal and perinatal outcomes. Early diagnosis, timely referral, adequate antenatal care, and availability of blood transfusion services are crucial in improving the survival and reducing complications.